Regulating Greenhouse Gas Emissions: The Supreme Court, the Environmental Protection Agency, Madison's "Auxiliary Precautions, " and Rohr's "Balance Wheel". (2nd April 2016) - Pautz, Michelle C.
Abstract : Regulating greenhouse gas emissions is a complicated task, exacerbated by the inability of the political institutions of government to provide clear guidance on this matter to the Environmental Protection Agency. Using the Madisonian notion of "auxiliary precautions, " it is argued that the EPA is in the best position to serve the public's interest in this area and should have more discretion in the absence of decisive action by the political branches of government. It is further argued that the EPA is in a position to embody Rohr's notion of a "balance wheel" to protect the nation from the harmful effects of greenhouse gas emissions.